The Adequacy of Kenya’s bank resolution framework in managing bank failures - Omundi, R. M. (Strathmore University, 2023)
An effective bank resolution framework is crucial to the realisation of financial stability in an economy. This flows from the appreciation that failure of one banking institution if not well managed could have a crippling effect to an entire banking industry and the financial system at large as witnessed during the global financial crisis. This study examines the egal and regulatory framework for resolving problem banks in Kenya to determine whether the framework is adequate to manage bank failures. In its analysis the study focuses on the statutory provisions encapsulated in the Banking Act, the Central Bank Act, the Kenya Deposit Insurance Act, the Companies Act 2015 and the relevant regulations and the role of the key resolution authorities. The need for existence of a special resolution framework at a national level to deal with problem banks as highlighted in this study cannot be overstated. The study evaluates the significant contributions of the Financial Stability Board in formulating guidelines and recommendations for an effective resolution regime against which the effectiveness of existing national bank resolution frameworks are bench marked. Reforms to the United States of America and the United Kingdom’s bank resolution regimes following the global financial crisis are analysed to draw lessons that could be applied to strengthen Kenya’s bank resolution regime. The findings from this study establish that despite the various reforms implemented to the bank resolution framework resting with the enactment of the Kenya Deposit Insurance Act in 2012 and the Companies Act 2015, the bank resolution process in Kenya has continued to be marred by delayed intervention by the resolution authorities, protracted legal disputes and inconsistency in judicial decisions. The study further establishes a lack of transparency, accountability and integrity in the resolution process. To this end, this study proposes various reforms to strengthen Kenya’s bank resolution framework in line with international best practices.
Full- text thesis